Educational and career goal attainments in young adult childhood cancer survivors. Issue 2 (April 2017) - Bashore, Lisa; Breyer, Emma
Abstract: Purpose: Examine the educational and career outcomes of young adult childhood cancer survivors. Design and Methods: Descriptive study design using a survey sent to 336 survivors. Quantitative and qualitative data were analyzed separately. Results: Only 50 completed surveys were returned. Having a central nervous system tumor and radiation were associated with physical impairments. Four themes also emerged: future as medical professionals, dreams fallen short, peer relationships, and positive outlook on life. Practice Implications: Pediatric nurses caring for survivors should partner with oncology professionals to support survivors to enrich their educational and career opportunities.